2017
DOI: 10.1002/cpdd.408
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Dose Pharmacokinetics of Oral Cannabidiol Following Administration of PTL101: A New Formulation Based on Gelatin Matrix Pellets Technology

Abstract: Cannabidiol (CBD) is the main nonpsychoactive component of the cannabis plant. It has been associated with antiseizure, antioxidant, neuroprotective, anxiolytic, anti-inflammatory, antidepressant, and antipsychotic effects. PTL101 is an oral gelatin matrix pellets technology-based formulation containing highly purified CBD embedded in seamless gelatin matrix beadlets. Study objectives were to evaluate the safety and tolerability of PTL101 containing 10 and 100 mg CBD, following single administrations to health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 33 publications
(115 reference statements)
6
49
1
Order By: Relevance
“…The absorption kinetics among oral capsule studies were highly variable. The variability may be explained by the various capsule formulations that were included in our study . Feeding status may also contribute to the variability of absorption kinetics among oral capsule studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption kinetics among oral capsule studies were highly variable. The variability may be explained by the various capsule formulations that were included in our study . Feeding status may also contribute to the variability of absorption kinetics among oral capsule studies.…”
Section: Discussionmentioning
confidence: 99%
“…The variability may be explained by the various capsule formulations that were included in our study. 11,13,17,[21][22][23][24] Feeding status may also contribute to the variability of absorption kinetics among oral capsule studies. The presence of food, especially with high-fat content, may slow gastric emptying and gastrointestinal (GI) motility, and therefore delay drug absorption and reduce Cmax.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 1 testing has been conducted on this product (10 to 100 mg) and found that it had significantly greater bioavailability compared to a reference product containing CBD (see Sativex® below). [85] Ananda Scientific (Israel) is producing pure CBD for medicinal purposes and reports having their Phase 1 pharmacokinetics studies underway presently in Israel, with numerous other trials planned in Israel and China. [86] In 2015, the US Food and Drug Administration (FDA) granted GW Pharmaceuticals Fast Track designation for intravenous CBD to treat Neonatal Hypoxic-Ischemic Encephalopathy (NHIE).…”
Section: Marketing Authorizations (As a Medicinal Product)mentioning
confidence: 99%
“…This finding is of great interest in regard to in vivo CYP3A inhibition by CBD because this threshold range for inhibition of EM clearance in vivo was similar to the reported Ki value of CBD inhibition against CYP3A in vitro (1 lM). 13 Atsmon et al 24 developed a new formulation for CBD by embedding purified CBD in a seamless gelatin matrix and used this formulation in humans. In their study, intestinal absorption of CBD from the gelatin matrix pellets was found to be faster than that from the conventional oromucosal spray, and the resultant AUCs of CBD at the single oral doses of 10 and 100 mg were determined to be 10.31 -4.14 and 153.0 -34.7 ng$h/mL (mean -SD; n = 14), respectively, 24 indicating that the increase in dose resulted in an increase of the AUC in a greater than doseproportional manner.…”
mentioning
confidence: 99%
“…13 Atsmon et al 24 developed a new formulation for CBD by embedding purified CBD in a seamless gelatin matrix and used this formulation in humans. In their study, intestinal absorption of CBD from the gelatin matrix pellets was found to be faster than that from the conventional oromucosal spray, and the resultant AUCs of CBD at the single oral doses of 10 and 100 mg were determined to be 10.31 -4.14 and 153.0 -34.7 ng$h/mL (mean -SD; n = 14), respectively, 24 indicating that the increase in dose resulted in an increase of the AUC in a greater than doseproportional manner. Therefore, it is suggested that the pharmacokinetic nonlinearity of CBD may also be observed in humans when the absorption process does not limit its bioavailability.…”
mentioning
confidence: 99%